Building blocks - Voigt, Cynthia (New York : Aladdin Paperbacks, 2002)
In a trip back in time, Brann meets his father as a ten-year-old and learns for the first time to love and understand him.
Book Links (A.L.A.).
Horn Book Starred.
School Library Journal.
6.8
5-8
Keywords: Fathers and sons -- Fiction; Science fiction; Time travel -- Fiction; Father-son relationship -- Fiction; Science fiction; Time travel -- Fiction